2020
DOI: 10.1002/mp.14345
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inter‐fraction target motion variations in the context of pencil beam scanned proton therapy in non‐small cell lung cancer patients

Abstract: For locally advanced-stage non-small cell lung cancer (NSCLC), inter-fraction target motion variations during the whole time span of a fractionated treatment course are assessed in a large and representative patient cohort. The primary objective is to develop a suitable motion monitoring strategy for pencil beam scanning proton therapy (PBS-PT) treatments of NSCLC patients during free breathing. Methods: Weekly 4D computed tomography (4DCT; 41 patients) and daily 4D cone beam computed tomography (4DCBCT; 10 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The largest variations were observed in IMPT_3D plans for D 1 (spine) for lung cancer patient 1 (42.67 2.38 ± Gy RBE ), and MHD for oesophageal cancer patient 11 (14. 43 1.51 Gy RBE ). ±…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest variations were observed in IMPT_3D plans for D 1 (spine) for lung cancer patient 1 (42.67 2.38 ± Gy RBE ), and MHD for oesophageal cancer patient 11 (14. 43 1.51 Gy RBE ). ±…”
Section: Resultsmentioning
confidence: 99%
“…For the oesophageal cancer patients, these did not exceed 9.1 ± 1.5 mm. By chance, this population of lung and oesophageal cancer patients, did not include 'big movers', which are not the most representative thoracic patients of the admissions in our radiotherapy clinic [43]. The target motion amplitudes reported in this study were quantified by the mean of all deformation vector lengths from DIR within the whole CTV (CTV of primary tumour and CTV of [multiple] pathological lymph nodes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides intra-fractional motion, the dose calculation in low-density lung tissue has large uncertainties and large inter-fractional changes are expected to occur [24,[51][52][53]. Each of these challenges are discussed separately in the following paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…Otter et al found that tumor amplitude changes were largest for lung patients with large tumor amplitudes, and they found changes in the amplitude up to 8.8 mm. 30 Applying a VW evaluation is a bit conservative since this evaluation is not based on a realistic error scenario, but instead the lowest (VWmin) or highest (VWmax) dose value in each voxel. The VWmin/ VWmax dose distributions can, therefore, result in a physically unrealizable dose distribution.…”
Section: Discussionmentioning
confidence: 99%